2013
DOI: 10.1016/j.bbalip.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Lysophospholipid receptor activation of RhoA and lipid signaling pathways

Abstract: The lysophospholipids sphingosine 1-phosphate (S1P) and lysophosphatidic acid (LPA) signal through G-protein coupled receptors (GPCRs) which couple to multiple G-proteins and their effectors. These GPCRs are quite efficacious in coupling to the Gα12/13 family of G-proteins, which stimulate guanine nucleotide exchange factors (GEFs) for RhoA. Activated RhoA subsequently regulates downstream enzymes that transduce signals which affect the actin cytoskeleton, gene expression, cell proliferation and cell survival.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 182 publications
(234 reference statements)
1
56
0
Order By: Relevance
“…LPA signals through its G-protein-coupled receptors, and so far, in humans, six LPA receptors (LPA [1][2][3][4][5][6] ) have been cloned and characterized (11)(12)(13)(14). Recent studies have demonstrated a positive role for LPA and LPA 1 in the pathogenesis of fibrosis (15,16).…”
mentioning
confidence: 99%
“…LPA signals through its G-protein-coupled receptors, and so far, in humans, six LPA receptors (LPA [1][2][3][4][5][6] ) have been cloned and characterized (11)(12)(13)(14). Recent studies have demonstrated a positive role for LPA and LPA 1 in the pathogenesis of fibrosis (15,16).…”
mentioning
confidence: 99%
“…Rho/ROCK signaling results in cellular responses, including modulation of gene transcription, rearrangement of the myosin-actin cytoskeleton, cell contraction, and fibrosis (Siehler, 2009;Kozasa et al, 2011;Knipe et al, 2015). S1P is a well established activator of the Rho/ROCK signaling pathway and is linked to multiple phenotypic changes in fibroblasts and vascular smooth muscle cells (Hu et al, 2006;Siehler, 2009;Xiang et al, 2013). S1P was shown to induce fibroblast-to-myofibroblast transformation and increase collagen expression via S1P 2 receptor-mediated Rho signaling in lung and cardiac fibroblasts (Urata et al, 2005;Gellings Lowe et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…60 Bioactive LPA regulates a wide variety of cellular processes, including cell proliferation, differentiation, migration, transcription, and survival, by activating different signaling pathways that are mediated by Ras, Rho, and Rac, adenylyl cyclase, PLC, PLD, AKT, and PI3 kinases. 48,52,[56][57][58]60 By activating these different intracellular molecules via their cognate GPCRs, lysophospholipids regulate multiple and redundant cellular processes. 60 LPA has been also shown to mediate its intracellular effects by regulating calcium influx and peroxisome proliferator-activated receptor-gamma nuclear receptor activity.…”
Section: 63mentioning
confidence: 99%
“…LPA and S1P act at the extracellular and intracellular levels, mediating their biological effects via different G-protein-coupled receptors (GPCRs), which are linked to the subunits of Ga12/13, Gq/11 and Gi heterotrimeric G-proteins. 45,48,51,60 There are several wellcharacterized and cognate subtypes of GPCRs for S1P and LPA, including S1P [1][2][3][4][5] and LPA [1][2][3][4][5][6] , respectively. 45,51,57 These different GPCRs belong to either EDG or P2Y receptor clusters and are expressed widely in different tissues and cell types.…”
Section: Lysophospholipids: Role In Physiological and Pathological Comentioning
confidence: 99%
See 1 more Smart Citation